Design and Construction of IoT-Based Temperature Monitoring Application for Server Room - Kanya Lailatul Ulya; Atikah Rakhmawati; Dinda Nasya Atin (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Maintaining optimal temperature in server rooms is critical to ensure the reliability and longevity of IT equipment. Overheating can lead to system failure, data loss, and increased maintenance costs. This study presents the design and implementation of an IoT-based temperature monitoring application tailored for server room environments. The system utilizes a DHT22 temperature and humidity sensor connected to an ESP32 microcontroller, which transmits real-time data to a cloud-based dashboard via Wi-Fi. The data is visualized through a web interface that allows administrators to monitor room conditions remotely and receive alerts when temperature thresholds are exceeded. The application was tested in a simulated server room environment over a two-week period. Results demonstrated stable performance with accurate temperature readings and reliable alert delivery. The system's scalability, low cost, and ease of deployment make it a practical solution for data centers, schools, or small businesses. This IoT-based approach offers an efficient and automated method to enhance server room monitoring and improve response time in managing thermal risks.